Identification of Factors Influencing the Development of Innovations and Inventions in Iranian Sports - Asghari Alaei, Hossein; Shojaei, Vahid; Hami , Mohammad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: In today’s world, creating movement and dynamism in business is not solely achieved through capital and a skilled workforce. The entrepreneur is a new player who provides the necessary dynamism for economic activities in today’s complex economy. The aim of this study was to identify the factors influencing the development of innovations and inventions in Iranian sports. Methods and Materials: The present research was conducted using a mixed-method approach. The first part was exploratory and conducted through exploratory factor analysis. The second part was qualitative, focusing on the opinions of experts. The sample in the quantitative section included 178 individuals, comprising sports management professors, ideators, inventors, entrepreneurs, and entrepreneurship and sports business instructors. They were selected through non-random snowball sampling and purposive non-random sampling. The qualitative section included 16 experts in the field of sports business and entrepreneurship. Data collection tools in the quantitative section included a valid and reliable 66-item researcher-made questionnaire, and in the qualitative section, in-depth individual interviews were conducted. Findings: The results indicated that six factors were identified by the sample members as influencing the development of sports innovations and inventions in Iran: managerial, intrinsic/infrastructural, procedural, economic, legal, and political. Together, these six factors explained approximately 74% of the variance in the development of sports innovations and inventions. Conclusion: Overall, it can be stated that attention to the factors influencing the development of inventions and innovations can pave the way for the development of sports in the country and create entrepreneurial opportunities in Iran’s sports industry.